Echo of everyday life or “wu-es-be” in experimental animation - Lipiński, Kamil (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article discusses animated works by Wojciech Bąkowski and the broader context of their origins addressing Jean-Luc Nancy’s philosophy of division of voices and its hermeneutical implications. Making explicit reference to these theoretical considerations, the author analyzes “Speaking Movies” by Bąkowski and his new productions for art galleries, employing digital tools to reinvestigate their meaning and interpret his autotelic recitation. The analysis follows several distinctive examples that highlight, via different experimental techniques, the interplay between verbal articulations, echo-like effects, and reverberations in the production of a differentiated audiovisual landscape.